Midwives’ Strategies in Preventing Stunting through Nutrition Education at Integrated Health Posts (Posyandu) - Mardiana Ginting; Nadia Nadia; Natasya Deswita (International Journal of Nursing and Midwifery Research, 2025)
Stunting remains a major public health problem that affects child growth and development, particularly during the first 1,000 days of life. In Indonesia, efforts to prevent stunting are closely linked to community-based health services, especially Integrated Health Posts (Posyandu), where midwives play a strategic role as frontline health workers. This study aims to explore midwives’ strategies in preventing stunting through nutrition education at Posyandu, focusing on the types of educational approaches used, levels of community participation, challenges encountered, and perceived impacts on maternal nutrition knowledge and practices. This research employed a qualitative descriptive design conducted at selected Posyandu in Karo Regency/North Sumatra. Participants included midwives, Posyandu cadres, and mothers of children under five, selected through purposive sampling. Data were collected through in-depth interviews, observations of Posyandu activities, and document analysis of nutrition education materials. The data were analyzed thematically to identify patterns and key themes related to midwives’ strategies and their effectiveness. Ethical principles, including informed consent, confidentiality, and voluntary participation, were strictly observed throughout the study. The findings indicate that midwives implement a variety of strategies, including individual counseling, group-based nutrition education, and home visits, supported by educational media such as posters, flipcharts, and food demonstrations. Major challenges included low attendance, limited resources, and cultural beliefs affecting feeding practices. Despite these challenges, nutrition education delivered by midwives contributed to improved maternal knowledge and positive changes in feeding behaviors. In conclusion, midwives integrated and context-sensitive strategies play a vital role in stunting prevention through nutrition education at Posyandu.